Studi Komparatif Aborsi: Analisis UU Nomor 1 Tahun 1946 dan UU Nomor 1 Tahun 2023 - Muhammad Fadhly Mubaraq; Nurlela Puspa Sari; Fuad Nur (Indo Publishing, 2026)
Abortion is a complex legal issue because it relates to medical, moral, religious, and human rights aspects. In Indonesian criminal law, the regulation of abortion crimes has changed with the enactment of Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code), which replaced the Old Criminal Code in Law Number 1 of 1946. This study aims to compare the provisions of abortion crimes in both regulations. The research method used is normative legal research with a statutory and comparative approach, through a literature review of primary and secondary legal materials. The results show that the Old Criminal Code criminalizes abortion almost absolutely without providing exceptions for medical or humanitarian reasons. In contrast, the National Criminal Code adopts a more contextual approach by continuing to qualify abortion as a criminal act but providing exceptions for abortions carried out in accordance with statutory provisions. This change reflects a paradigm shift in criminal law toward protecting humanitarian values and substantive justice